2023
DOI: 10.3390/ph16101355
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gut Microbiome Community Mitigates Multiple Sclerosis in a Mouse Model: The Promising Role of Palmaria palmata Alga as a Prebiotic

Shimaa Mohammad Yousof,
Badrah S. Alghamdi,
Thamer Alqurashi
et al.

Abstract: Background: Red marine algae have shown the potential to reduce inflammation, influence microbiota, and provide neuroprotection. Objective: To examine the prebiotic properties of Palmaria palmata aqueous extract (Palmaria p.) and its potential as a neuroprotective agent in multiple sclerosis (MS). Methods: eighty-eight adult Swiss mice were divided into four male and four female groups, including a control group (distilled water), Palmaria p.-treated group (600 mg/kg b.w.), cuprizone (CPZ)-treated group (mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…An intervention study of the probiotic Saccharomyces boulardii in 40 MS patients found significant reductions in levels of the inflammatory marker high-sensitivity C-reactive protein along with pain intensity and fatigue, as well as significant improvements in terms of the Quality of Life Scale, and the GHQ Somatic and Social Dysfunction subscales in the probiotic group compared to the placebo group ( Asghari et al, 2023 ). Palmaria palmata Alga probiotic intervention in mice in a CPZ model increased Firmicutes/Bacteroidetes ratio, increased the abundance of beneficial Lactobacillus, Proteobacteria, and Bactriodia communities, and prevented CPZ-induced grip strength loss and open field test anxiety, as compared to the control group ( Yousof et al, 2023 ). Anti-inflammatory-antioxidant-rich diet and co-supplemented synbiotics intervention in 69 patients with MS significantly reduced Faecal calprotectin levels at 6 months, reduced intestinal inflammation, and improved clinical manifestations in progressive forms of MS compared with the control group ( Moravejolahkami et al, 2023 ).…”
Section: Treatment Strategies and Future Prospectsmentioning
confidence: 99%
“…An intervention study of the probiotic Saccharomyces boulardii in 40 MS patients found significant reductions in levels of the inflammatory marker high-sensitivity C-reactive protein along with pain intensity and fatigue, as well as significant improvements in terms of the Quality of Life Scale, and the GHQ Somatic and Social Dysfunction subscales in the probiotic group compared to the placebo group ( Asghari et al, 2023 ). Palmaria palmata Alga probiotic intervention in mice in a CPZ model increased Firmicutes/Bacteroidetes ratio, increased the abundance of beneficial Lactobacillus, Proteobacteria, and Bactriodia communities, and prevented CPZ-induced grip strength loss and open field test anxiety, as compared to the control group ( Yousof et al, 2023 ). Anti-inflammatory-antioxidant-rich diet and co-supplemented synbiotics intervention in 69 patients with MS significantly reduced Faecal calprotectin levels at 6 months, reduced intestinal inflammation, and improved clinical manifestations in progressive forms of MS compared with the control group ( Moravejolahkami et al, 2023 ).…”
Section: Treatment Strategies and Future Prospectsmentioning
confidence: 99%
“…The study delves into the potential of Palmaria palmata (Rhodophyta) (Figure 4) as a prebiotic in mitigating MS through the modulation of the gut microbiome community in a mouse model [106]. Multiple sclerosis is a complex autoimmune disorder characterized by the immune system attacking the central nervous system.…”
Section: Evidence Of Neuroprotection In Preclinical Studiesmentioning
confidence: 99%
“…The findings underscore the intricate relationship between the gut microbiome and immune function, suggesting that interventions targeting gut microbial communities could offer novel therapeutic avenues for managing autoimmune diseases such as MS. This research contributes to the growing body of evidence supporting the therapeutic potential of prebiotics and highlights the need for further exploration into their mechanisms of action and clinical applications in autoimmune disorders [106]. The study investigates the neuroprotective effects of agaropentaose (hydrolysates of agarose isolated from red algae) against 6-hydroxydopamine (6-OHDA)-induced neurotoxicity in SH-SY5Y cells.…”
Section: Evidence Of Neuroprotection In Preclinical Studiesmentioning
confidence: 99%
“…For instance, it was shown that peptides obtained by protein hydrolysis could potentially be used in the formulations of pharmaceuticals and nutraceuticals as an antidiabetic agent [10]. A recent study even discovered the role of nutrients in the seaweed to make it a promising prebiotic to be potentially used as a neuroprotective agent in multiple sclerosis patients [11].…”
Section: Introductionmentioning
confidence: 99%